2023
DOI: 10.1158/2767-9764.crc-22-0238
|View full text |Cite
|
Sign up to set email alerts
|

On the Choice of Longitudinal Models for the Analysis of Antitumor Efficacy in Mouse Clinical Trials of Patient-derived Xenograft Models

Abstract: In translational oncology research, the Patient Derived Xenograft (PDX) model and its use in Mouse Clinical Trials (MCT) are increasingly described. This involves transplanting a human tumor into a mouse and studying its evolution during follow-up or until death. A MCT contains several PDXs in which several mice are randomized to different treatment arms. Our aim was to compare longitudinal modeling of tumor growth using mixed and joint models. Mixed and joint models were compared in a real MCT (N=225 mice) to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…For each scenario, 500 simulated datasets were generated. Tumor growth kinetics were simulated using a two classes mixed model with a class-specific linear trajectory, a class-specific treatment effect and individual random intercept and slope 15 . These datasets were then analyzed with a 2-class LCMM model as described in a previous section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each scenario, 500 simulated datasets were generated. Tumor growth kinetics were simulated using a two classes mixed model with a class-specific linear trajectory, a class-specific treatment effect and individual random intercept and slope 15 . These datasets were then analyzed with a 2-class LCMM model as described in a previous section.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, it has been applied in the study of cognitive decline 14 . In a previous work, we demonstrated that linear and non-linear mixed-effects models could robustly estimate treatment effect in a MCT design 15 . Therefore, our objective was to explore the performances of the LCMM method to classify treatment trajectories in PDX models.…”
Section: Introductionmentioning
confidence: 97%